Estimating mRNA lengths from Plasmodium falciparum genes by Virtual Northern RNA-seq analysis. Issue 1 (January 2016) - Shaw, Philip J.; Kaewprommal, Pavita; Piriyapongsa, Jittima; Wongsombat, Chayaphat; Yuthavong, Yongyuth; Kamchonwongpaisan, Sumalee
Graphical abstract: Highlights: Virtual Northern RNA-seq was conducted for Plasmodium falciparum. Estimates of major transcript length are described for 3052 genes. Novel polycistronic/overlapping transcripts were identified. Abstract: Accurate gene models are essential for understanding parasite biology. However, transcript structure information is lacking for most parasite genes. Here, we describe "Virtual Northern" analysis of the malaria parasite Plasmodium falciparum to address this issue. RNA-seq libraries were made from size-fractionated RNA. Transcript sizes for 3052 genes were inferred from the read counts in each library. The data show that for almost half of the transcripts, the combined untranslated regions are more than twice the length of the open reading frame. Furthermore, we identified novel polycistronic, or gene overlapping, transcripts that suggest revisions to current gene models are needed.